Absolute Quantitative Evaluation of 67Ga Scintigraphy in Lupus Nephritis. (June 2016) - Tsai, Shih-Chuan; Hsieh, Tsu-Yi; Huang, Ping-Wun; Lin, Wan-Yu
Abstract : Purpose: Renal biopsy is crucial for management of lupus nephritis. However, it is invasive and can cause bleeding and infection. In our previous study, we developed a semiquantitative method for gallium renal imaging and demonstrated a good correlation between the left kidney-to-spine ratio (K/S ratio) and the results of renal biopsy. However, the accuracy of left K/S ratio is compromised by the variation of spinal gallium uptake, especially in patients with extraordinarily high or low gallium uptakes in the spine. In this study, we developed an absolute quantitative method and compared the results of quantitative gallium images, semiquantitative gallium images, visual methods, and renal biopsies. Methods: Thirty-four patients with lupus nephritis were enrolled and underwent renal biopsy to determine activity index (AI) and chronicity index. A delayed 48-hour gallium scan was also performed and interpreted by visual, semiquantitative, and absolute quantitative methods. For absolute quantitative analysis, a standard solution with activities of approximately 555 KBq (15 μCi) was prepared and poured into a 5-mL tube, which was placed close to the patient. ROIs were drawn around the outer edge of the left kidney as well as around the outer edges of the standard. A kidney uptake index (KUI) was calculated, and the results were compared with K/S ratio, visual grading, and renal biopsies. Results: Kidney uptake index had the best correlation with AI among the 3 methods using Spearman rank correlation test. The Spearman R values were 0.78, 0.71, and 0.61 for KUI, K/S ratio and visual grading, respectively. Chronicity index did not correlate well with the results of any of the 3 methods. In addition, AI was significantly higher in patients with a KUI equal to or greater than 1.5, when compared with patients with a KUI lower than 1.5 ( P = 0.00001 by Mann-Whitney U test). Using a K/S ratio of 0.95 as a cutoff value, AI also showed a statistically significant difference with P = 0.0001. When a visual grading of 2 was used as a cutoff value, P = 0.0008. The difference in AI was most significant when the statistical value was based on the KUI. Conclusions: The KUI showed better correlation with the results of renal biopsy than the K/S ratio and the visual grading. We suggest that the KUI from the absolute quantitative renal gallium scintigraphy may be a useful parameter for evaluating the disease activity in lupus nephritis.